Graphene: Room‐Temperature Colossal Magnetoresistance in Terraced Single‐Layer Graphene (Adv. Mater. 37/2020). Issue 37 (15th September 2020) - Hu, Junxiong; Gou, Jian; Yang, Ming; Omar, Ganesh Ji; Tan, Junyou; Zeng, Shengwei; Liu, Yanpeng; Han, Kun; Lim, Zhishiuh; Huang, Zhen; Wee, Andrew Thye Shen; Ariando, Ariando
Abstract : Similar to placing a carpet on a staircase, terraced graphene is formed by stacking a layer of graphene on an atomically terraced substrate. This leads to topographic corrugations and charge puddles in the terraced graphene. In the presence of a magnetic field, its resistance can change as high as 5000% at room temperature, paving a route for extremely sensitive and high‐resolution magnetic sensors, as revealed by Ariando Ariando and co‐workers in article number 2002201 .